Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1990
DOI: 10.1115/90-gt-380
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of a Low NOx LBG Combustor Using Bypass Air

Abstract: A 150-MW, 1300°C (1573 K) class gas turbine combustor firing coalgasified fuel has been designed. Main purpose of the present paper is first to estimate CO and NOx emissions, and second to discuss the low NOx combusion technology burning such a low-BTU gas. The full-scale, atmospheric-pressure combustion tests were conducted over a wide range of conditions using bypass air.The results are summarized as follows: (1) A designed combustor has an excellent combustion efficiency of 99.6 percent even when the calori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…The examples also compare the influence of fuel burned. For both cases four fuels were examined: methane and three different coal derived fuels, G1 -G3 (De la Mora et al , 1985, Nakata et al , 1990, whose composition is reported in The pressure ratios of the two gas turbines (the T.I.T. being essentially the same) led, as expected, to higher efficiency levels for the LM 1600, while the heavy duty turbine presents better values for specific power and second law efficiency, that make possible a more favorable use in combined plants (Table 2).…”
Section: Gas Turbinementioning
confidence: 99%
See 2 more Smart Citations
“…The examples also compare the influence of fuel burned. For both cases four fuels were examined: methane and three different coal derived fuels, G1 -G3 (De la Mora et al , 1985, Nakata et al , 1990, whose composition is reported in The pressure ratios of the two gas turbines (the T.I.T. being essentially the same) led, as expected, to higher efficiency levels for the LM 1600, while the heavy duty turbine presents better values for specific power and second law efficiency, that make possible a more favorable use in combined plants (Table 2).…”
Section: Gas Turbinementioning
confidence: 99%
“…In fact, some tendencies which could improve performance would also cause a very high increase in emissions. Hence, the systems for NO x abatement are proving to be increasingly more expensive as regards both the more accurate fluid-dynamic design of combustion chamber (mainly in the case of dry combustors) and the consumption of demineralized injected water or steam (Aoyama and Mandai, 1984, Cerri and Arsuffi, 1988, Fitts et al , 1990, Nakata et al , 1990, Sato et al, 1990, Kreitmeier at al., 1991.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the CDG fuel has a low heating value and contains a high percentage of inert gases, its flame temperature is low. Figure 1 compares adiabatic flame temperatures of LBG and CH 4 . The flame temperature of CH4, with air preheated at 370°C, reaches its highest level of 2100°C.…”
Section: Nomenclaturementioning
confidence: 99%